The Relationship between Age of Menarche and Body Mass Index (BMI) with Endometriosis Incidence at Dr. Mohammad Hoesin Palembang Period 2018 – 2020 - Usman, Fatimah; Ghina Reza S; Eka Handayani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Endometriosis is the presence of endometrial glands and stroma outside the uterus. This study aims to analyze the relationship between age of menarche and body mass index (BMI) with the incidence of endometriosis. Methods. This study is an analytical observational study with a cross-sectional approach. The samples taken in this study were post-operative patients with gynecological disorders at Dr. Mohammad Hoesin General Hospital Palembang. The sample taken in this study was 62 respondents during the period 2018-2020 with a simple random sampling technique based on inclusion criteria. The research data was processed and analyzed by univariate and bivariate with Chi-square test using SPSS application. Results. Most of the respondents with endometriosis experienced at the age of menarche <12 years (91.3%) and had a non-obese BMI (73.3%). There was a significant relationship between the age of menarche and the endometriosis incidence (p=0.039). There was no statistically significant relationship between body mass index (BMI) and the endometriosis incidence (p=1,043). Conclusion. Early menarche can increase the risk of endometriosis. The majority of women with endometriosis in this study had a BMI in the non-obese category (BMI <25).